Content accuracy and reliability of pulmonary nodule information on social media platforms: a cross-platform study of YouTube, Bilibili, and TikTok - Zhou, Yunanji; Zeng, Xiang; Yuan, Ting; Wang, Qian; Wu, Siqi; Du, Lei; Wang, Lihua; He, Jun (Frontiers in Medicine, 2025)
BackgroundPulmonary nodules (PNs) are often overlooked, potentially leading to health risks. Social media platforms are increasingly used for health information dissemination. This study evaluates the quality and engagement of PN-related videos on YouTube, Bilibili, and TikTok.MethodsOn March 1, 2025, we searched each platform using “pulmonary nodule” or its Chinese equivalent. After screening, 271 videos were analyzed. Video characteristics were documented, and quality was assessed using PEMAT, VIQI, GQS, and mDISCERN tools. Inter-rater reliability was high (κ = 0.81).ResultsThe final sample included 98 (YouTube), 74 (Bilibili), and 99 (TikTok) videos. TikTok videos were the shortest (median 114 s) yet had the highest engagement. Nonprofit organizations dominated YouTube uploads; physicians were most common on Bilibili and TikTok. Treatment was the most covered topic. YouTube scored highest in comprehensibility and actionability (PEMAT-T/A), while Bilibili and TikTok scored higher in production quality (VIQI, GQS). Video quality did not differ significantly between professional and non-professional uploaders. Most quality metrics showed weak correlation with audience engagement.ConclusionLong-form platforms (YouTube and Bilibili) offer higher-quality PN information but lower engagement, whereas short-form platforms (TikTok) show high interaction but lower informational depth. Social media can play a supportive role in public PN education. We provide recommendations for creators, platforms, and viewers to improve the quality and reliability of medical content.